Pelatihan Karya Tulis Ilmiah (KTI) bagi Penghulu Guna Meningkatkan Kompetensi dalam Menulis - Muzakkir Muzakkir; Said Fadhlain; Rena Juliana; Samwil Samwil (Universitas Teuku Umar, 2021)
The Ministry of Religions' success indicator for religious advice is reflected in the level of the community's satisfaction index with the performance of the head of the KUA in providing an excellent service to the community. For this reason, it is important to promote academic work for the headmen that is the result of researching or studying Islamic marriage law, developing the headmen, or improving the services of the KUA in areas related to the headmen. The results achieved through this community service activity are fostering the talents and interests of the headmen in writing and the creativity in improving their writing skills, at least encouraging them to write as a Muslim intellectual tradition. As evidence, there were several headmen who submit assignments in the form of scientific writing for guidance. In addition, the results of this activity add to the nuances and insights of the headmen in writing and learn how to write scientific writing techniques in the form of journals and books as a link between society and government and vice versa.